Clinical Presentation, Histological Findings and Prevalence of Helicobacter pylori in Patients of Gastric Carcinoma (Faridpur Medical College Journal, 2011)
Carcinoma stomach is the second leading cause of cancer death worldwide. This study was undertaken to determine the clinical and pathological profile of carcinoma stomach in Bangladesh and to find out the prevalence of H. pylori infection in carcinoma stomach subjects. Patients with carcinoma stomach confirmed on histopathology were included in the study. Data were recorded regarding demography, clinical features, blood group of the patients, location and macroscopic type of the cancer at endoscopy. Three to five biopsies from non-necrosed region and two paired biopsies from non-cancerous part of stomach were taken. One piece of each paired specimen was placed in the urea-agar media for CLO test and the other piece was used for histological examination. Out of 50 patients, 64% were male and 36% were female. The mean age was 51.05±14.98 years. Common presenting complains were dyspepsia/ abdominal pain, vomiting and dysphagia; abdominal mass, metastatic lymph node and ascites were predominant signs. About one third (34%) patients had blood group A. About 50% cancer was located in antrum followed by antrum and body (24%), then body (18%), fundus and body (4%) and fundus (4%). In 56% cases the lesion was ulcerative followed by polypoid (34%) and ulceroinfiltrative (10%). Histopathologically 52% was intestinal type, 28 % was diffuse type 20% was poorly differentiated adenocarcinoma. The prevalence of H. pylori in overall carcinoma stomach cases was 60% but individually in intestinal type 88%, in diffuse type 57% and in poorly differentiated type 50%. Key words: Carcinoma stomach; Helicobacter pylori. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9205 FMCJ 2011; 6(2): 78-81